Pioneers of chromosome elimination - Comai, Luca; Marimuthu, Mohan Prem Anand (Frontiers in Epigenetics and Epigenomics, 2025)
Epigenetic traits are persistent cellular and organismal properties that do not result from changes in DNA sequence. One such property involves transmission of chromosomes, which entails the formation of highly specialized chromatin structures, the kinetochores, on selected chromosomal regions, called centromeres. Centromere function is essential and centromeres are determined epigenetically by the deposition of a variant histone H3 CENP-A (CENH3 in plants). Either reduced or ectopic function alone leads to genome instability, decreased fitness, aneuploid syndromes, and cancer. At times, however, centromeres malfunction in an apparently programmed mode. This is exemplified by a peculiar centromeric syndrome involving selective elimination of a chromosome set, which can affect a wide range of organisms, including plants. Over half a century ago, plant geneticists described this syndrome in interspecific crosses of barley. Building on their work, we examine the growing understanding of how CENH3 function can be modified to affect epigenetic regulation of centromeres.